The South Platte: old river - new course? Changes in land and water use in the South Platte Basin - Martin, Lindsay, editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 2001)
Abstracts of papers presented at the10th annual South Platte forum on October 27-28, 2001 at the Raintree Plaza Conference Center in Longmont, Colorado.
Proceedings of the 10th annual South Platte forum
Brief abstracts of papers presented.
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Integrated water development -- South Platte River Valley (Colo. and Neb.) -- Growth -- Congresses; Water use -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water resources development -- South Platte River Valley (Colo. and Neb.) -- Congresses; Land use -- South Platte River Valley (Colo. and Neb.) -- Congresses